Stereoselective synthesis and antimicrobial activity of steroidal C-20 tertiary alcohols with thiazole/pyridine side chain - Shingate, Bapurao B.; Liazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V. (European Journal of Medicinal Chemistry, 2011)
Stereoselective synthesis of novel steroidal C-20 tertiary alcohols with thiazole and pyridine side chain using Grignard reaction of steroidal ketones and thiazole/pyridine magnesium bromide have been realized. These molecules were evaluated in vitro for their antifungal and antibacterial activities. Most of the compounds exhibited significant antifungal and antibacterial activity against all the tested strains. (C) 2011 Elsevier Masson SAS. All rights reserved.
Keywords: antibacterial activity; Antifungal activity; Grignard reaction; Steroid side chain; Steroidal ketones